Et l’Espagne frémit de peur. L’âge d’or du cinéma d’horreur ibérique à la fin du franquisme (1968–1976) - Guermond, Valentin (Romanica Silesiana)
In the present article, the author discusses the ideology in some Spanish horror movies made between 1968 and 1976, during the last years of the dictatorship of Francisco Franco. The Spanish horror production, also called fantaterror, seems to be an indicator of the problematics of Spanish society. Indeed, it seems that the outbreaks of violence and eroticism of these films relate to the double face of the last years of the dictatorship, that of hedonism and of the repression of desires. By examining the specific aesthetic of the fanta‑terror and its narrative duality between Good and Evil, we want to show that behind the apparent entertainment these movies are inherently shaped by Franco’s regime. They deserve to be evaluated in terms of political, economic and cultural conditions in which they were created. Key words: horror movies, fantasy, Spain, Franco’s dictatorship, ideology in film